Targeted Anticancer Agent with Original Mode of Action Prepared by Supramolecular Assembly of Antibody Oligonucleotide Conjugates and Cationic Nanoparticles - Victor Lehot; Patrick Neuberg; Manon Ripoll; François Daubeuf; Stéphane Erb; Igor Dovgan; Sylvain Ursuegui; Sarah Cianférani; Antoine Kichler; Guilhem Chaubet; Alain Wagner (Pharmaceutics, 2023)
Despite their clinical success, Antibody-Drug Conjugates (ADCs) are still limited to the delivery of a handful of cytotoxic small-molecule payloads. Adaptation of this successful format to the delivery of alternative types of cytotoxic payloads is of high interest in the search for novel anticancer treatments. Herein, we considered that the inherent toxicity of cationic nanoparticles (cNP), which limits their use as oligonucleotide delivery systems, could be turned into an opportunity to access a new family of toxic payloads. We complexed anti-HER2 antibody-oligonucleotide conjugates (AOC) with cytotoxic cationic polydiacetylenic micelles to obtain Antibody-Toxic-Nanoparticles Conjugates (ATNPs) and studied their physicochemical properties, as well as their bioactivity in both in vitro and in vivo HER2 models. After optimising their AOC/cNP ratio, the small (73 nm) HER2-targeting ATNPs were found to selectively kill antigen-positive SKBR-2 cells over antigen-negative MDA-MB-231 cells in serum-containing medium. Further in vivo anti-cancer activity was demonstrated in an SKBR-3 tumour xenograft model in BALB/c mice in which stable 60% tumour regression could be observed just after two injections of 45 pmol of ATNP. These results open interesting prospects in the use of such cationic nanoparticles as payloads for ADC-like strategies.